Synthesis and antitumor mechanisms of two novel platinum(ii) complexes with 3-(2′-benzimidazolyl)-7-methoxycoumarin. Issue 8 (7th August 2018) - Qin, Qi-Pin; Wang, Shu-Long; Tan, Ming-Xiong; Wang, Zhen-Feng; Huang, Xiao-Ling; Wei, Qing-Min; Shi, Bei-Bei; Zou, Bi-Qun; Liang, Hong
Abstract : Pt2 is a novel telomerase inhibitor binding to c-myc promoter elements, which arrests the cell cycle at the G2/M phase and induces apoptosis and causes mitochondrial dysfunction. Abstract : Two novel platinum(ii ) complexes, [PtCl2 (H-MeOBC )(DMSO)] (Pt1 ) and [Pt2 Cl3 (MeOBC)(DMSO)2 ] (Pt2 ), with 3-(2′-benzimidazolyl)-8-methoxycoumarin (H-MeOBC ) as the ligand were synthesized and evaluated for their antiproliferative activity. Among all the tumor cells, dual-Pt(ii ) complexPt2 exhibited the most potent activity, with an IC50 value of 0.5 ± 0.2 μM against cisplatin-resistant SK-OV-3/DDP cancer cells. In the case of SK-OV-3/DDP cells, Pt2 displayed a 20.1–196.0-fold increased activity when compared with cisplatin, H-MeOBC andPt1 . Importantly, Pt1 andPt2 displayed low inhibitory rates against normal HL-7702 cells. Further investigation revealed thatPt2 is a novel telomerase inhibitor binding to c-myc promoter elements. Mechanistic studies demonstrated that dual-Pt(ii ) complexPt2 arrests the cell cycle at the G2/M phase and induces apoptosis and causes mitochondrial dysfunction.